Bacterial-viral Urine Microbiota in Uncomplicated Recurrent Infection of the Lower Urinary Tract: Results of Pilot Study - Ju. L. Naboka; M. I. Kogan; S. V. Mordanov; Kh. S. Ibishev; A. V. Ilyash; I. A. Gudima (Вестник урологии, 2020)
Introduction. Difficulties in the management and treatment of patients with uncomplicated recurrent lower urinary tract infection (LUTI) are largely because bacterial, viral and other components remain unexplored in the etiological structure of the disease.Purpose of the study. To study the urine bacterial-viral associations in uncomplicated recurrent infections of the lower urinary tract (LUT).Materials and methods. The study included 14 patients with uncomplicated recurrent infections of the LUT, the average age was 33.0 ± 4.7 years. The object of the study was the average portion of morning urine collected prior to the appointment of empirical antibiotic therapy. Urine was divided into 3 aliquots: 1 for general urine analysis, 2 for bacteriological examination, 3 for polymerase chain reaction (PCR).Results. Aerobic-anaerobic associations were found in urine in all cases. Enterobacteriaceae family representatives were discovered in 92.8% of cases; they were represented by E. coli (78.6%), Klebsiella spp. (14.2%), Proteus spp. (7.1%). Moreover, in one patient at the same time (7.1%) E. coli + Klebsiella spp was isolated from urine.The gram-positive microflora pattern consisted of 7 genera and / or species and in various combinations was found in all patients. The taxonomic structure of the gram-positive flora was represented by E. faecalis (64.3%), S. lentus (21.4%), Corynebacterium spp., S. warneri, E. faecium (14.3% each), S. epidermidis + E. coli was recorded in 4 (28.6%) women, E. faecalis + E. faecium + E. coli + Klebsiella spp. - in 1 (7.1%), E. faecalis + E. faecium + E. coli also in 1 (7.1%) patients.Non-clostridial anaerobic bacteria (NAB) were isolated from urine in all cases with Eubacterium spp dominating. (57.1%). The taxonomic structure of NAB was represented by 5 genera: Eubacterium spp., Peptostreptococcus spp., Peptococcus spp., Bifidobacterium spp., Propionibacterium spp.Viruses were detected in urine in 6 (42.9%) patients. Epstein-Barr virus (EBV) was detected in 4 (28.6%) of them, moreover, in 1 case, in association with human papillomavirus (HPV53), in two other cases (7.1% each), cytomegalovirus (CMV) was verified and human herpes simplex virus type 6 (HHV6), respectively.Conclusions. In patients with uncomplicated recurrent LUTI, viruses with a prevalence of EBV were verified in urine in 42.9% of cases (28.6%). Apparently, the treatment of this patients` cohort should be directed not only to the bacterial, but also the viral components of the urinary microbiota.